Kepatuhan Persyaratan Fungsional Pengendalian Hak Akses pada OLA (Office Letter Automation) Berdasarkan ISO 16175-2: 2011 - Faturohmah, Trina Nur; Fachmi, Achmad (UI Scholars Hub, 2023)
This research discusses the compliance of PT X's Office Letter Automation (OLA) system with the functional requirements for controlling access rights based on ISO 16175-2 2011. PT X has been using the system since 2019, OLA is a web-based application used to control correspondence and other activities. Electronic records management in PT X. This research aims to identify whether OLA meets EDRMS standards related to access rights or access control. This research uses a qualitative approach by studying literature and making observations to identify the implementation accuracy according to the ISO 16175-2:2011 standard requirements, which is examined with OLA as the research object. The research results show that of the 17-access control functional requirements, OLA can fulfill 16 mandatory requirements. So, it does not meet the minimum standards required by the standards and is included in the major findings. For this reason, organizations need to take corrective and preventive actions so that OLA can comply with the ISO 16175-2 2011 standard requirements. However, overall, OLA is good enough to support electronic security management activities, especially for security systems in the access rights section.